S. Freud's and C. Jung's approaches to creativity from today's perspective - Almonaitiene, Junona (Psichologija, 1995)
The S. Freud's and C. Jung's approaches to creativity are presented briefly in this article and an attempt to evaluate them from today's perspective is given. Some results of contemporary empirical researches induce the new interest to these classical approaches. Their wideness, globality, attention to the real creative works of the well-known authors seem to be the important positive traits, especially in comparison with many rather petty contemporary experimental researches concerning creativity. The revelation of the problem of creativity's unconscious motives is the most important desert of S. Freud and C. Jung. It seems to the author, nevertheless, that the S. Freud's creativity explanation gives wider perspective to further explorations in comparison with Jung's.
Keywords: Jung; Freud; creativity